Photocatalysis technology for treating petroleum wastewater and the potential application of tapered bubble column (TBC) : A review - Abdulla, Firdos M.; Shnain, Zainab Yousif; Alwasiti, Asawer A.; Abid, Mohammad Fadhil; Azhari, Nour Hamid Abduelraman (Global NEST, 2024)
The photocatalytic oxidation of organic and petroleum wastewater treatment is an advanced oxidation process (AOP) with several benefits. It operates at normal temperatures and pressure, is inexpensive, does not produce secondary waste, and us easily accessible. Many studies have employed bubble columns, slurry bubble columns, and three-phase fluidized reactors in the photocatalytic process for wastewater treatment. Pure TiO2 and Fe-doped TiO2 are considered the most promising catalysts. The aim of this work is to review the main factors affecting the photocatalytic process of organic pollutants and petroleum wastewater (produced water) treatment, photocatalysts type, with a special focus on pure TiO2 and Fe-doped TiO2, light source, and reactor type.